2018
DOI: 10.3917/redp.285.1013
|View full text |Cite
|
Sign up to set email alerts
|

Does the Literature Support a High Willingness to Pay for Green Label Buildings? An Answer with Treatment of Publication Bias

Abstract: Increasing attention is being paid to the building sector due to its importance in the climate change debate. In recent years, a growing literature on the price premium paid by consumers to access more energy efficient and sustainable buildings has emerged as a common topic in hedonic model estimations. In this paper, we aim to provide a summary of this literature by conducting a metaanalysis of more than 50 studies from around the world. In this way, based on a random effects models and weighted OLS robust cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 70 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…If comparing the overall combined effect (4.20%) obtained in this document with similar studies, it is found that the first meta-analysis in 2014 obtained a premium of 7.6% [19], and the second in 2016 obtained 4.3% [20], while the third in 2018 had a range of values from 3.5-4.5% [22]. It is observed that the premium obtained in this study is coherent with other studies and the mean effect of the premium has stabilized.…”
Section: Analysis-1mentioning
confidence: 78%
See 4 more Smart Citations
“…If comparing the overall combined effect (4.20%) obtained in this document with similar studies, it is found that the first meta-analysis in 2014 obtained a premium of 7.6% [19], and the second in 2016 obtained 4.3% [20], while the third in 2018 had a range of values from 3.5-4.5% [22]. It is observed that the premium obtained in this study is coherent with other studies and the mean effect of the premium has stabilized.…”
Section: Analysis-1mentioning
confidence: 78%
“…Another problem found in this research is the lack of data in the existing studies, which complicates and restricts the use of the meta-analysis, as indicated by authors such as [22] and [115].…”
Section: Analysis-1mentioning
confidence: 99%
See 3 more Smart Citations